2021
DOI: 10.3390/cancers13184625
|View full text |Cite
|
Sign up to set email alerts
|

Targeting OLFML3 in Colorectal Cancer Suppresses Tumor Growth and Angiogenesis, and Increases the Efficacy of Anti-PD1 Based Immunotherapy

Abstract: The role of the proangiogenic factor olfactomedin-like 3 (OLFML3) in cancer is unclear. To characterize OLFML3 expression in human cancer and its role during tumor development, we undertook tissue expression studies, gene expression analyses of patient tumor samples, in vivo studies in mouse cancer models, and in vitro coculture experiments. OLFML3 was expressed at high levels, mainly in blood vessels, in multiple human cancers. We focused on colorectal cancer (CRC), as elevated expression of OLFML3 mRNA corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 65 publications
0
15
0
Order By: Relevance
“…We screened a set of target genes whose expression was reversed in ROBO1 E280* cells compared with ROBO1 WT cells ( Figure 6A ). Among these genes, RT-qPCR and western blotting analysis verified that OLFML3, which plays a role in tumor-related angiogenesis ( 21 , 22 ), was decreased in the ROBO1 WT group, while it was recovered in the ROBO1 E280* group ( Figures 6B, C ). Subsequently, we detected OLFML3 mRNA expression in clinical samples.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…We screened a set of target genes whose expression was reversed in ROBO1 E280* cells compared with ROBO1 WT cells ( Figure 6A ). Among these genes, RT-qPCR and western blotting analysis verified that OLFML3, which plays a role in tumor-related angiogenesis ( 21 , 22 ), was decreased in the ROBO1 WT group, while it was recovered in the ROBO1 E280* group ( Figures 6B, C ). Subsequently, we detected OLFML3 mRNA expression in clinical samples.…”
Section: Resultsmentioning
confidence: 89%
“…Through RNA sequencing, we screened differentially expressed genes and found that OLFML3 expression was downregulated by ROBO1 WT and recovered by ROBO1 E280* . OLFML3, a member of the olfactomedin domain-containing secreted glycoprotein family, was reported to be involved in neovascular formation during embryonic development and tumor progression ( 21 , 22 , 34 , 35 ). Miljkovic et al reported that targeting OLFML3 suppressed tumor growth via impairing angiogenesis and pericyte coverage ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…As IL-6 is necessary and sufficient for PD-L1 induction [ 48 ], we speculate that therapeutic targeting of Olfml3 may enhance current immunotherapeutic approaches for GBM patients. In support of this hypothesis, recent work has demonstrated that anti-OLFML3 therapy in conjunction with anti-PD1 immunotherapy increased overall survival in a mouse model of colorectal cancer [ 21 ]. Thus, inhibition of microglial Olfml3 , in tandem with immune checkpoint blockade, may yield improved patient survival in GBM.…”
Section: Discussionmentioning
confidence: 98%
“…Importantly, OLFML3 has broad relevance to cancer progression. OLFML3 is a disease biomarker in colon cancer [ 19 ] and has been shown to promote neoangiogenesis [ 20 , 21 ], epithelial-to-mesenchymal transition [ 22 ], and metastasis [ 22 ] in several cancers.…”
Section: Introductionmentioning
confidence: 99%
“…This association is also supported by human eQTL studies in breast cancer, suggesting that rs3903072 may alter Ovol1 expression ( Li et al, 2014 ). Targeting Olfml3 has been shown to suppress tumor growth and angiogenesis ( Stalin et al, 2021 ). Of the non-DE genes, Zmiz1 is a prognostic marker of multiple cancer types ( Mathios et al, 2019 ), Rpl37a is a biomarker for response to neoadjuvant chemotherapy in non-metastatic locally advanced breast cancer ( Carrara et al, 2021 ), and Hipk1 has been shown to act as a tumor suppressor by activating p53 ( Rey et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%